Coastal Dynamic and Evolution - Anfuso, Giorgio; Rizzo, Angela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes papers published in the Special Issue titled "Coastal Dynamic and Evolution", which aimed to collect multidisciplinary studies that involved the evaluation of coastal evolution at different temporal scales, from hours and days to months and years, as well as historical changes. The volume contains investigations carried out by means of aerial photos and satellite images, as well as results from in situ surveys and observations aimed at assessing morphological changes in shoreline and dune systems as a consequence of chronic flooding and erosion processes or the occurrence of specific weather-related events. Studies on the evaluation of past and future sea-level variations and related impacts have also been included. In order to provide the reader with a wide overview of different coastal settings and methodological approaches, case studies from Russia, Italy, California (USA), Morocco, Spain, Indonesia, Ireland and Colombia have been included in this Special Issue. The content may be of interest to those who perform a wide range of investigations related to coastal analysis and management, especially to researchers and academics who can exploit the provided approaches and methodologies.